A robust path following algorithm based on the orthogonal Bishop parametrization for a non-holonomic mobile manipulator - Mazur, Alicja; Dyba, Filip (Zielona Góra: Uniwersytet Zielonogórski)
We deal with the fundamental problem of path following applied to control mobile manipulators. A parametric-based path following algorithm is proposed. Such an approach results in a cascaded structure of the control system, so that the control algorithm is designed using the backstepping integrator method.
Keywords: backstepping integrator control; non-holonomic mobile manipulator; orthogonal Bishop parametrization; singularity avoidance; path following algorithm; sliding mode controller